Research on coach-athlete relationship and team performance based on 3Cs theory: the chain mediating role of emotional intelligence and athletic engagement - Pan, Fangfang; Sui, Wenjie (Frontiers in Psychology, 2025)
In the Chinese cultural context, the coach-athlete relationship has a certain hierarchical structure, is dominated by coach-centered formal training, and its development is influenced by history and culture. Based on the 3Cs theory, this study constructs a mechanism model of how coach - athlete relationship impacts team performance. Using structural equation modeling, multilevel path analysis was conducted on 1,566 cross-sport athletes. By introducing two mediating variables, emotional intelligence and athletic engagement, the study explores the path of coach-athlete relationship on team performance. The research reveals that coach-athlete relationship exerts a notably positive influence on team performance (β = 0.556, p < 0.001), whose path of action showed a triple transduction dimension. Emotional intelligence has an independent mediating effect of 0.049 (p < 0.001). Athletic engagement shows an independent mediating effect of 0.094 (p < 0.001). The chained mediating effect amounts to 0.014 (p < 0.001). Results suggest that improving coach-athlete relationship, it can help to improve athletes’ emotional intelligence and engagement levels, thereby promoting team performance, which offers specific strategies and methods to boost team performance, holding great theoretical and practical significance.